A Domino Oxidation/Arylation/Protodecarboxylation Reaction of Salicylaldehydes: Expanded Access to meta‐Arylphenols. Issue 3 (25th June 2015) - Luo, Junfei; Preciado, Sara; Araromi, Solomon Olatokunbo; Larrosa, Igor
Abstract: A method that allows salicylaldehydes to be efficiently transformed into meta ‐arylated phenol derivatives through a cascade oxidation/arylation/protodecarboxylation sequence is presented. We demonstrate that the aldehyde functional group can be used as a convenient removable directing group to control site selectivity in C−H activation. Aldehydes are easily introduced into the starting materials and the group is readily cleaved after the C−H functionalization event. Abstract : Any weather is PEPPSI weather : A method that allows salicylaldehydes to be efficiently transformed into meta ‐arylated phenol derivatives through a cascade oxidation/arylation/protodecarboxylation sequence is presented. We demonstrate that the aldehyde functional group can be used as a convenient removable directing group to control site selectivity in C−H activation.